A Subdivision Based Iterative Collocation Algorithm for Nonlinear Third-Order Boundary Value Problems. (9th June 2016) - Ejaz, Syeda Tehmina; Mustafa, Ghulam
Abstract : We construct an algorithm for the numerical solution of nonlinear third-order boundary value problems. This algorithm is based on eight-point binary subdivision scheme. Proposed algorithm is stable and convergent and gives more accurate results than fourth-degree B-spline algorithm.